Monitoring the agri-food system in Myanmar: Mechanization Service Providers – July 2024 survey round - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
Agricultural mechanization service providers (MSPs) are crucial for enabling smallholder farmers to undertake a range of power-intensive farm and post-harvest operations in a timely manner. These operations are essential for food production and farm income. MSPs are capital-intensive operations. The economic viability of these businesses is highly sensitive to (1) capacity utilization, which generates the cash flow needed to repay equipment loans; (2) prices of imported capital goods, including machines, equipment, and fuels; and (3) availability of machine operators, among others. Hence, the operations of MSPs are sensitive to restrictions on mobility and trade.